Progressive resistance training in young people with Prader-Willi syndrome: protocol for a randomised trial (PRESTO). Issue 12 (22nd December 2022) - Shields, Nora; Bennell, Kim L; Southby, Alesha; Rice, Lauren J; Markovic, Tania; Bigby, Christine; Prendergast, Luke; Watts, Jennifer J; Schofield, Cara; Loughnan, Georgina; Franklin, Janet; Levitt, David; et al.
Abstract : Introduction: Preliminary evidence suggests that progressive resistance training may be beneficial for people with Prader-Willi Syndrome (PWS), a rare genetic condition that results in muscle weakness and low muscle tone.To establish whether community-based progressive resistance training is effective in improving the muscle strength of people with PWS; to determine cost-effectiveness; and, to complete a process evaluation assessing intervention fidelity, exploring mechanisms of impact, understanding participant experiences and identifying contextual factors affecting implementation. Methods and analysis: A multisite, randomised controlled trial will be completed. Sixty participants with PWS will be randomised to receive either progressive resistance training (experimental) or non-progressive exercise (placebo control). Participants will be aged 13 to 60 years, be able to follow simple instructions in English and have no contraindications to performing progressive resistance training. The experimental group will complete progressive resistance training two times weekly for 24 weeks supervised by an exercise professional at a community gym. The control group will receive all aspects of the intervention except progressive overload. Outcomes will be assessed at week 25 (primary endpoint) and week 52 by a blinded assessor. The primary outcome is muscle strength assessed using one repetition maximum for upper limb and lower limb. Secondary outcomes are muscle mass, functional strength, physical activity, community participation, health-related quality of life and behaviour. Health economic analysis will evaluate cost-effectiveness. Process evaluation will assess safety and intervention fidelity, investigate mechanism of impact, explore participant experiences and identify contextual factors affecting implementation. Data collection commenced in February 2020 and will conclude in September 2023. Ethics and dissemination: Ethical approval was obtained from The Royal Children's Hospital Human Research Ethics Committee (HREC/50874/RCHM-2019) under the National Mutual Acceptance initiative. Research governance approvals were obtained from five clinical sites. Results will be disseminated through published manuscripts, conference presentations, public seminars and practical resources for stakeholder groups. Trial registration number: ACTRN12620000416998; Australian and New Zealand Clinical Trial Registry.